Consent Study In Europe : A Study Case to Understand Development of Digital Consent In UK - Sekarwati; Nashir, Asep Kamaluddin; Rai, I Nyoman Aji Suadhana; Ghofur, Abdul (FISIP UPNVJ, 2023)
The securitization of cyberspace has been specter to the political studies in various countries. This article focusses on the dynamic of speech act on implementation consent and its relation to the theory of lateral pressure formulated by Nazli in studying cyberpolitcs. Since 2018 European Commission has implemented GDPR as a basic law related to data transfer, collect and process (TCP). This policy has brought the fundamental problem to the activity conducting by the state and private sector. Moreover, it was also criticized that this policy has brought to the discrimination of algorithm that came to bias to the minority group. In speak of Methodology, we used qualitative research of 418 article with keyword ‘consent’ focusing in Social and Humanities Science on Journal Sage, after manually analysis found 146 articles related to the consent study and social science. The final project is to find out the significant tendency on how Europe has securitized GDPR through speech act by corelating it to the Lateral Pressure Index. The potential implications of the finding could give theoretical preference in formulating data protection base policy.